Special paperRemote ischaemic conditioning in percutaneous coronary intervention: a meta-analysis of randomised trials - Niu, Xiaowei; Zhang, Jingjing; Chen, De; Wan, Guozhen; Zhang, Yiming; Yao, Yali (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : It remains uncertain whether remote ischaemic conditioning (RIC) using cycles of limb ischaemia-reperfusion as a conditioning stimulus benefits patients undergoing percutaneous coronary intervention (PCI). Aim: We performed a meta-analysis toassessthe effect of RIC in PCI. Material and methods : The PubMed, EMBASE, Web of Science, and CENTRAL databases were searched for randomised controlled trials (RCTs) comparing RIC with controls. The treatment effects were measured as a pooled odds ratio (OR), standardised mean difference (SMD), and corresponding 95% confidence intervals (95% CIs) using random-effects models. Results : Fourteen RCTs, including 2,301 patients, were analysed. Compared to the controls, RIC significantly reduced the cardiac enzyme levels (SMD = –0.21; 95% CI: –0.39 to –0.04; p = 0.015; heterogeneity test, I2 = 75%), and incidence of PCI-related myocardial infarction (OR = 0.70; 95% CI, 0.51–0.98; p = 0.037). There was a trend toward an improvement in the complete ST-segment resolution rate with RIC (OR = 1.83; 95% CI: 0.99–3.40; p = 0.054). No significant difference could be detected between the two groups regarding the risk for acute kidney injury after PCI. Univariate meta-regression analysis suggested that the major source of significant heterogeneity was the PCI type (primary or non-emergent) for the myocardial enzyme levels (adjusted R2 = 0.44). Subsequent subgroup analysis confirmed the results. Conclusions : The present meta-analysis showed that RIC could confer cardioprotection for patients undergoing coronary stent implantation. Moreover, the decrease in the myocardial enzyme levels was more pronounced in the patients treated with primary PCI.